A Case in Favour of Radicalisation: a Commentary on Issues Surrounding the Caldicott Report - Matthew Owen (Opticon1826, 2010)
The premise of this commentary is that the terms ‘radical’ and ‘radicalisation’ need to be defended. These terms are being unfairly bracketed with ‘violent extremism’. Extremist atrocities, whether implemented by terrorist groups (e.g. destruction of the Twin Towers) or governments (e.g. Hitler’s final solution), are just those: atrocities to be condemned. Radicalism, however, is a desire to bring about substantive change, and in its simplest form this term is divorced from any moral or ethical connotation. I will contextualize this debate using the example of Umar Farouk Abdulmutallab, the former University College London (UCL) student charged with attempting to blow up a US airliner. A discussion of what is meant by radicalisation will follow, after which some examples of well-known radicals will be presented. Finally, I shall argue that contemporary society is ‘bust’ and that we need radical ideas and radical people in order to ‘fix’ our future society. As such, we need radicalisation within society in general and universities in particular.
Keywords: atrocities; radical politics